Regeneration and Reuse of Biomaterial for the Removal of Cadmium Ions from Waste Water - Kour, Jagjit (Journal of Institute of Science and Technology, 2016)
The nitrogen functionalized biomaterial is used for the adsorption of Cd (II) from waste water. The application and possibility of regeneration and reuse of functionalized biomaterial were evaluated with adsorption desorption experiments. Cd (II) loaded biomaterial was eluted with sodium hydroxide, nitric acid, and hydrochloric acid. Among them 0.1 M nitric acid gave the most effective result releasing about 90% of metal ions onto the solution in six successive cycles. The result suggests the efficiency and applicability of functionalized biomaterial as a potential biosorbent in the removal of Cd (II) from waste water. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, Page: 90-94